An Improved Method of FM Radio Channel Selection for a Passive Radar System Based on Signal Environment Analysis - Inhwan Jeong; Sanhae Kim; Hyungyu Kwak; Jonghwan Lee; Kyuha Song (IEEE Access)
This study proposes an improved method of frequency modulation (FM) radio channel selection for a passive radar system based on signal environment analysis. Passive radar has numerous advantages over conventional active radar, such as survivability, low cost, and low design complexity owing to a lack of its own transmitter, as well as the capability to detect low radar cross section targets. However, its performance depends on the properties of the illuminators it exploits. Therefore, a passive radar must select proper FM radio channels to achieve better performance. We analyze the time-varying characteristics of FM radio channel content, signal interference, and signal distortion that occur in real-world operating environments. Based on these environment analyses results, proper FM radio channels can be selected. We conducted experiments in real-world environments and compared the test results obtained using the proposed method with those achieved via analytical methods based on the sensitivity of receiver to validate the proposed method. The results demonstrate that the proposed method enhances detection performance.